PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN PADA PT. POS INDONESIA MEDAN - Mangasa Panjaitan; Selamat Siregar (Universitas Methodist Indonesia, 2021)
Customers are one of the main components in every business activity, where business actors have a duty to create consumer loyalty which aims to increase company revenue. Consumer loyalty can be influenced by circumstances that give rise to benefits after using it, so that business actors need to create a safe environment and optimal service so that customers feel interested and comfortable when making transactions. The purpose of this study is to determine the effect of service quality on consumer loyalty at PT. POS Indonesia, Medan. The sample size is 97 respondents. The method of analysis in this study is to use a simple linear regression model. The results showed that service quality has a positive and significant effect on consumer loyalty at PT. Pos Indonesia with a value of Fcount of 255,702 > Ftable of 3.04 and a value of t-count of 15,991 is greater than the t-table (1,623). Changes in consumer loyalty can be explained by changes in service quality variables of 72.90%, while the remaining 27.10% is explained by other variables that are not included as variables in the study.